Solvent‐Dependent Structure of Iridium Dihydride Complexes: Different Geometries at Low and High Dielectricity of the Medium. Issue 12 (16th February 2016) - Polukeev, Alexey V.; Marcos, Rocío; Ahlquist, Mårten S. G.; Wendt, Ola F.
Abstract: The hydride iridium pincer complex [(PCyP)IrH2 ] (PCyP= cis ‐1, 3‐bis[(di‐ tert ‐butylphosphino)methyl]cyclohexane, 1 ) reveals remarkably solvent‐dependent hydride chemical shifts, isotope chemical shifts, J HD and T 1 (min), with r HH increasing upon moving to more polar medium. The only known example of such behaviour (complex [(POCOP)IrH2 ], POCOP=2, 6‐( t Bu2 PO)2 C6 H3 ) was explained by the coordination of a polar solvent molecule to the iridium ( J. Am. Chem. Soc .2006, 128, 17114). Based on the existence of an agostic bond between α‐C−H and iridium in1 in all solvents, we argue that the coordination of solvent can be rejected. DFT calculations revealed that the structures of1 and [(POCOP)IrH2 ] depend on the dielectric permittivity of the medium and these compounds adopt trigonal‐bipyramidal geometries in non‐polar media and square‐pyramidal geometries in polar media. Abstract : Controlled geometries : Dramatic non‐specific solvation‐induced geometry changes within iridium pincer complexes are reported. These compounds tend to adopt trigonal‐bipyramidal geometries in non‐polar media and square‐pyramidal geometries in polar media (see scheme).